Protein applications in sports nutrition-part I: Requirements, quality, source, and optimal dose - McLain, T. A.; Escobar, K. E.; Kerksick, C. M. (Strength and Conditioning Journal, 2015)
Protein, a key macronutrient, is needed by the body to repair and build new cellular structures. Exercising individuals participating in both aerobic and anaerobic activities require greater amounts of protein (1.2-1.6 g·kg ·d1) in their diet. Protein quality is evaluated primarily by essential amino acid content (8-12 g) and digestibility corrected amino acids (pdcaa) scores (1.0-1.2+). Flesh (beef, pork, poultry, and fish), dairy (whey, casein, milk, and cheese), egg, and plant (vegetable, soy, etc.) Range in quality (pdcaas: 0.74-1.2+) and other properties that further impact health. Optimal dosing (20-25 g; 8-12 g essential amino acids) is important to maximally stimulate muscle protein synthesis and promote a positive muscle protein balance.